(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2020)
In the last 10 years, in Latin America in general and Argentina in particular, socio-community practices have been institutionalized in university education, they integrate extension with teaching and research. Despite its short time, there has already been a significant number of experience reports that it would be impossible to even mention it; but the proportion of works destined to create tools that make it possible to analyze this type of practice is lower. Taking into account this panorama, in this work a provisional theoretical-methodological tool is outlined, which allows the analysis of socio-community practices. This tool helps to unveil the political, territorial, human and epistemological foundations that sustain it, contributes to assessing actions based on intentionality and makes it possible to continue building new knowledge, which is why it constitutes a heuristic tool.